NILAI KARAKTER DALAM CERITA RAKYAT ASAL MULA RAWA UMBUNG DAN RELEVANSINYA UNTUK PEMBELAJARAN BAHASA INDONESIA - Neti Erlina; Mastiah Mastiah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study is based on the importance of strengthening character education through contextual learning based on local culture. This study aims to examine the character values ​​contained in the folktale